Al-Masoudi School (785 AH - ... =…- 1383 AD) Baghdad School in the Jalayiri Era (Journal of the College of Basic Education, 2023)
Schools were considered among the most prominent points of communication and knowledge and cultural exchange, and the title of civilizational advancement, east and west. .) A study of one of the Baghdad schools during the Mongol rule period. There were tendencies for some of the Mongol sultans and their rulers in Iraq to restore the glories of Baghdad and what it was during the prosperous Abbasid eras, especially in the scientific and cultural aspects. Some links and mosques to what they were in the past, albeit with a simple thing. Some also built and established new schools, links and libraries that took on their Arab-Islamic character in administration and architecture... A number of their sultans and governors emerged in this aspect, including the governor Atta Malik al-Juwayni and those who had A connection with them, including al-Juwayni's wife, who worked on the establishment of the Asmatiyah school and related things - and I dealt with it in a previous research - which applies to the following periods, including the period of the Jalairi rule (740-813 AH = 1339-1410 AD) during the reign of Sultan Owais (760-777 AH / 1358-1375 A.D.) where the Al-Masudi school was established, the subject of the research, which was established by Khawaja Masoud bin Sadid Al-Dawla, who was one of those close to the governors of Iraq, and he had cultural interests represented in calligraphy and knowledge of the writings of previous nations, as well as his practice of some administrative functions.. and the school was established alongside it in Baghdad Al-Morjaniya, which was established by Khawaja Marjan in the year 758 AH = 1356 AD and others, relied in the research on late historical sources whose events reached the eighth century AH = the fourteenth century AD, including a book summarizing the Majma’ al-Adab by Ibn al-Futi, which included a study of events in Baghdad after the Mongol invasion and the conditions of its schools and scholars, and a book The Ghayathi history, which dealt with the historical events of the Mongol era in general from the year (656-891 AH / 1258-1486 AD), including the events that preceded and followed the establishment of the school in the year 785 AH, and the political and administrative changes witnessed during the Mongol rule ... We also do not forget the importance of modern references Which dealt with the study of the administrative and political conditions and the scientific and urban conditions that permeated them, including the book Encyclopedia of the History of Iraq between the two occupations, especially Part 2 and Part 3, and the book The Ilkhanid State. One of the references that had a clear impact in codifying the news of the Al-Masudi school is the subject of the research..The research was divided into several topics, the first of which dealt with determining the time period of the Mongol Ilkhani or Jalairi rule, and then dealt with the following topics, a summary of the life of its founder, Khawaja Masoud bin Sadid Al-Dawla, and then Studying the establishment of the school and its internal organization, and reviewing the news received about its library and comparing it with the schools that were established in the period under study.